Risk and protective factors in the origin of atrial septal defect secundum--national population-based case-control study - Csáky-Szunyogh, Melinda; Vereczkey, Attila; Urbán, Róbert; Czeizel, Andrew E (Central European journal of public health, 2014)
The aim of this study was to assess the risk factors in the origin of lethal or surgically corrected isolated atrial septal defect secundum. The population-based Hungarian Case-Control Surveillance of Congenital Abnormalities (conducted between 1980 and 1996) comprised 472 atrial septal defect secundum cases, 678 matched controls and 38,151 available controls without any defects; in addition, 21,022 malformed controls with other isolated defects. Medically recorded chronic disorders in the prenatal maternity logbook were evaluated, while acute maternal diseases, drug treatments and pregnancy supplements were analyzed on the basis of both prospective medically recorded data and retrospective maternal information. Acute pelvic inflammatory disease, paroxysmal supraventricular tachycardia and phenolphthalein treatment due to severe constipation of mothers were shown to contribute to the development of atrial septal defect secundum of their children. High doses of folic acid in early pregnancy had positively influenced a minor part of isolated atrial septal defect secundum in foetuses. In conclusion, the obvious genetic predisposition for atrial septal defect secundum is connected with maternal paroxysmal supraventricular tachycardia and triggered by acute pelvic inflammatory diseases and phenolphthalein treatment, while the manifestation of atrial septal defect secundum can be reduced by high doses of folic acid supplementation in early pregnancy.
Keywords: Tachycardia, Supraventricular; paroxysmální tachykardie; Female; novorozenec; rozpomínání; ženské pohlaví; supraventrikulární tachykardie; Folic Acid; lidé; Infant, Newborn; defekty septa síní; Phenolphthalein; Self Report; surveillance populace; Mental Recall; těhotenství; studie případů a kontrol; fenolftalein; zkreslení výsledků (epidemiologie); Risk Factors; Bias; Heart Septal Defects, Atrial; matky; Case-Control Studies; Mothers; komplikace těhotenství; pánevní zánět; Population Surveillance; rizikové faktory; Hungary; Pregnancy Complications; Tachycardia, Paroxysmal; zpráva o sobě; Maďarsko; Pregnancy; Pelvic Inflammatory Disease; kyselina listová; Humans